2002
DOI: 10.1021/bi0265325
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the First Fungal NADP-GAPDH from Kluyveromyces lactis

Abstract: Deletion of the phosphoglucose isomerase gene, PGI1, in Saccharomyces cerevisiae leads to a phenotype for which glucose is toxic. This is related to overproduction of NADPH through the oxidative part of the pentose phosphate pathway and the incompetence of S. cerevisiae to deal with this overproduction. A similar deletion (rag2) in Kluyveromyces lactis does not lead to such a phenotype. We transformed a genomic library of K. lactis in a yeast vector to a S. cerevisiae strain with a pgi1 deletion and screened f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
44
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(45 citation statements)
references
References 22 publications
1
44
0
Order By: Relevance
“…GDP1 of Kluyveromyces lactis is a phosphorylating GAPDH, unique among nonplant eukaryotes, that can rescue the lethal phenotype of the PGI1 deletion in S. cerevisiae (17). When growing on pentoses, K. lactis avoids carbon exhaust by inducing the expression of this enzyme; GDP1 interferes with the interplay of glycolysis and the PPP by switching the glycolytic redox-cofactor from NAD(H) to NADP(H) (17,18).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…GDP1 of Kluyveromyces lactis is a phosphorylating GAPDH, unique among nonplant eukaryotes, that can rescue the lethal phenotype of the PGI1 deletion in S. cerevisiae (17). When growing on pentoses, K. lactis avoids carbon exhaust by inducing the expression of this enzyme; GDP1 interferes with the interplay of glycolysis and the PPP by switching the glycolytic redox-cofactor from NAD(H) to NADP(H) (17,18).…”
Section: Resultsmentioning
confidence: 99%
“…When growing on pentoses, K. lactis avoids carbon exhaust by inducing the expression of this enzyme; GDP1 interferes with the interplay of glycolysis and the PPP by switching the glycolytic redox-cofactor from NAD(H) to NADP(H) (17,18). 2-DG tolerance was examined in the presence of GDP1.…”
Section: Resultsmentioning
confidence: 99%
“…Metabolic engineering of xylose metabolism would benefit on finding a mechanism for production of NADPH upstream in metabolism through a route, which would not result in loss of carbon. For example simultaneous deletion of glucose-6-phospate dehydrogenase encoding gene (Jeppsson et al, 2002) and expression of a partly NADPH-dependent glyceraldehyde 3-phosphate dehydrogenase encoding gene could direct the flow of carbon directly towards pyruvate and ethanol without the loss of carbon (Verho et al, 2002;Verho et al, manuscript in preparation). By using solely metabolic flux analysis it was not possible to study the effects of xylose uptake or pentose phosphate reactions, since their role as a limiting step originates from their kinetic properties such as K m values for uptake and Gibbs free energies for pentose phosphate pathway and thus cannot be studied in the present steady-state model.…”
Section: Discussionmentioning
confidence: 99%
“…From our proteomics results, we found that of the three GapDH isoenzymes in yeast, Tdh3p was the most highly expressed. We thus replaced TDH3 with either an NADPH-producing GapDH from Kluyveromyces lactis (KlGapDH) (Verho et al, 2002), or a non-phosphorylating GapDH from Bacillus cereus (BcGapN) in the baseline yL405 strain. Neither resulting strain produced more fatty alcohols than the parent (Fig.…”
Section: Optimizing Nadph/nadp+ and Nadh/nad+ Cofactor Usagementioning
confidence: 99%